Another tool in the experimental toolbox: On the use of aluminum as a substitute for chert in North American prehistoric ballistics research and beyond. (April 2022) - Eren, Metin I.; Mukusha, Lawrence; Lierenz, Julie; Wilson, Michael; Bebber, Michelle R.; Fisch, Michael; True, Trent; Kavaulic, Michael; Walker, Robert S.; Buchanan, Briggs; Key, Alastair
Experimental archaeology continues to mature methodologically and theoretically. Around the world, practitioners are increasingly using modern materials that would have been unavailable to prehistoric people in archaeological experiments. The use of a modern material substitute can offer several benefits to experimental method, design, control, replicability, feasibility, and cost, but it should be directly compared to its "traditional" analogue to understand similarities and differences. Here, aluminum is introduced as a substitute for chert in prehistoric ballistics research because, critically, aluminum is safe, inexpensive, easy to process, and it and chert possess densities that differ by less than 4%. The aluminum casting process for replicating stone artifacts is presented, and it is shown that the aluminum castings are essentially identical in form, flake-scar patterning, and mass to their stone counterparts. We then present a proof-of-concept ballistics experiment that demonstrates no difference between aluminum and stone points in terms of target penetration.